Spiritual Approach and Tiered Counselling as a Non-Pharmacological Therapy to Control Smoking Behavior of Elderly Women in Dieng - Taufik, Muhammad; Widiyaningsih, Dwi; Muhammad Hidayat Noor; Rizal Al Hamid; Hasbi Ni’ami Sihab (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: The religious atmosphere and various efforts to prevent smoking behavior in the Dieng Plateau have not raised awareness of smoking cessation, especially for elderly female smokers, even though the number of Acute Respiratory Tract infections and chronic respiratory disorders is increasing. To reduce smoking behavior, tiered counseling efforts and spiritual approaches can be used as alternative steps. Objectives: This research was to determine the reduction in smoking rates among elderly women in the Dieng Plateau after being given a spiritual approach as a non-pharmacological therapy. Methods: The type of research used was a quasi-experiment that provided pharmacological therapy (spiritual approach) to the control and intervention groups. Results: The research results showed that the smoking reduction rate was more significant after being given the spiritual approach intervention than the tiered counselling. The mean knowledge of the spiritual approach group was (95.37) and the tiered counselling group was (91.96) with a mean difference of 3.41. Therefore, health promotion using a spiritual approach is more effective in increasing the willingness of elderly women to control their smoking behavior compared to the multi-level counseling media. Conclusion: This study concludes that a spiritual approach is more effective than tiered counselling in reducing smoking rates among elderly female smokers in the Dieng Plateau. However, integrating both methods can better empower elderly women to control their smoking behavior and improve their overall health outcomes.